Improvement of Tomato Physiological Performance, Growth, and Yield Formation Under Salinity Stress Through Photosynthetic Bacteria Application - Christanto, Victor Satrio; Avianto, Yovi; Susila, Wisnu Adhi; Sari, Nur Kartika (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2026)
Tomato production is frequently constrained by salinity because salt stress restricts water uptake, chlorophyll maintenance, biomass formation, and yield. This study evaluated the effectiveness of the photosynthetic bacterium Rhodobacter sphaeroides BCK1 in improving tomato growth and physiological performance under salinity stress. A 3 × 3 factorial experiment combining three NaCl concentrations (0, 3.000, and 6.000 ppm) and three bacterial suspension doses (0, 10, and 20 ml L-1) was arranged in a completely randomized design with five replicates, resulting in 45 experimental units. Growth, biomass, yield, leaf greenness, relative water content, net assimilation rate, and relative growth rate were evaluated. Salinity significantly reduced most growth, yield, and physiological traits, whereas bacterial application improved these parameters. At 6.000 ppm NaCl, the application of 20 ml L-1 R. sphaeroides BCK1 increased leaf area by approximately 45%, root dry weight by 64%, fruit number by 55%, total fruit weight by 94%, and relative growth rate by 6,5% compared with uninoculated plants exposed to the same salinity level. Net assimilation rate was not significantly affected by salinity (P = 0,337) but increased with bacterial dose (P = 0,0096). The strongest overall response was obtained at 20 ml L-1, indicating that R. sphaeroides BCK1 can partially alleviate salinity-induced reductions in tomato growth and productivity.